AUTONOMOUS SYSTEMS IN TOURISM: APPLICATION OF SWARM ROBOTICS TECHNOLOGY FOR OPERATIONAL OPTIMIZATION IN INDONESIAN TOURIST DESTINATIONS - Indah Sulistiani; Rafi’i; Syarifuddin; Cut Ita Erliana; Dahlan Abdullah (CV. Adiba Aisha Amira, 2025)
Tourism in Indonesia continues to evolve as a vital sector in the economy, yet faces complex challenges in optimizing operational efficiency at tourist destinations. This research explores the application of autonomous systems and swarm robotics technology as an innovative solution to enhance operational efficiency. Autonomous systems, leveraging artificial intelligence and automation, collaborate with the adaptive principles of swarm robotics to create dynamic solutions for managing long queues, security, and mobility in tourist destinations. Through case studies and testing technology implementation at specific destinations, this research reveals the positive contributions of these systems to visitor experiences and operational efficiency. The implications of these findings extend to Indonesia's broader tourism sector, offering potential improvements in competitiveness and sustainability. The research details the potential development of swarm robotics technology in the future and highlights aspects that warrant further investigation. Thus, the approach of autonomous systems and swarm robotics becomes a practical solution and a strategic foundation for redefining tourism operations in Indonesia.